Case Report: An extremely rare penile shrapnel injury - Pan, Renbing; Liu, Jingwen; Wan, Lijun; Zhu, Jianyong (Frontiers in Pediatrics, 2024)
Penile shrapnel injuries are an exceedingly rare occurrence and a medical emergency.Herein, we present a case of penile shrapnel wounds in an adolescent male and discuss the management and complications associated with penetrating injuries to penile. We reported that an 18-year-old Chinese armed police soldier underwent debridement, shrapnel removal and suturing under spinal anesthesia. Six days postoperatively, he was discharged from the hospital smoothly. The patient reported normal erectile function and urination following discharge. With a follow-up of three months, the patient exhibited no symptoms of dysuria or erectile dysfunction. It is explicitly stated that prompt surgery intervention described in this report resulted in optimal prognosis. Penile shrapnel injury is a rare phenomenon typically associated with emergency drill and military training involving explosive shells. With regard to penetrating penile injury, timely surgical exploration is essential because it avoids penile plaque formation, penile fibrosis and angulation, and accelerates the return to erectile and urination function.